A pair of transposons coordinately suppresses gene expression, independent of pathways mediated by siRNA in Antirrhinum. Issue 2 (28th November 2012) - Uchiyama, Takako; Hiura, Satoshi; Ebinuma, Izuru; Senda, Mineo; Mikami, Tetsuo; Martin, Cathie; Kishima, Yuji
Summary: Our knowledge is limited regarding mechanisms by which transposable elements control host gene expression. Two Antirrhinum lines, HAM2 and HAM5, show different petal colors, pale‐red and white, respectively, although these lines contain the same insertion of transposon Tam3 in the promoter region of the nivea ( niv ) locus encoding chalcone synthase. Among 1000 progeny from HAM5 grown under the preferred conditions for the Tam3 transposition, a few showed an intermediate petal color between HAM2 and HAM5. Transposon tagging using these progeny identified a causative insertion of Tam3 for the HAM5 type (white) petal color, which was found 1.6 kb downstream of the niv gene. Insertion of Tam3 at the position 1.6 kb downstream of niv alone showed nearly wildtype petal pigmentation, and the niv expression reduced by only 50%. Severe suppression of niv observed in HAM5 required interaction of two Tam3 copies on either side of the niv coding sequence. DNA methylation and small interfering RNAs (siRNAs) were not associated with the suppression of niv expression in HAM5. Insertion of a pair of transposons in close proximity can interfere with the expression of gene located between the two copies, and also provide evidence that this interference is not directly associated with pathways mediated by siRNAs.